Preparation method of all-plastic polyurethane plastic track with controllable foaming bottom

By using soaked water in a fully plastic polyurethane plastic runway to generate carbon dioxide bubbles, controllable foaming at the bottom is achieved, site density and hardness problems are solved, and soft elastic structures are formed on the upper layer and the service life and construction efficiency are improved. .

CN119159736APending Publication Date: 2024-12-20SHANDONG YIBORUN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411299532.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

When the existing fully plastic polyurethane plastic runway materials are added too much powder, the site density is high, the hardness is high, and the comfort of use is reduced. It is difficult to control the traditional foaming method, which can easily lead to damage to the overall foaming structure surface layer and affect the service life. .

Method used

Add quartz sand soaked in water to the polyurethane A/B material mixture, and use the moisture reaction of quartz sand to generate carbon dioxide bubbles. By controlling the addition amount of quartz sand and pretreatment method, controllable foaming at the bottom is formed to form an upper layer and compact lower layer. Foaming structure.

Benefits of technology

The upper and lower soft elastic structure of the site is realized, which reduces the overall density, saves material usage, extends the service life, and avoids site damage caused by overall foaming, simplifies the construction process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119159736A_ABST
    Figure CN119159736A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an all-plastic polyurethane plastic runway with controllable foaming at the bottom, and belongs to the technical field of plastic runways. According to the invention, the quartz sand soaked in water is added into the polyurethane A / B material mixture, and the properties of the quartz sand and the polyurethane A / B material mixture are utilized to complete foaming and curing at the same time, so that a structure with a dense and firm upper layer and a foamed and soft lower layer is formed, and the situation that a site is easy to damage due to integral foaming is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic runways, and in particular relates to a method for preparing a fully plastic polyurethane plastic runway with controllable foaming at the bottom. Background Art

[0002] Polyurethane tracks, also known as all-weather athletic tracks, are internationally recognized as the best all-weather outdoor sports surface material. They offer excellent flatness, high compressive strength, appropriate hardness and elasticity, and stable physical properties. These features facilitate athletes' speed and technique, effectively improving athletic performance and reducing fall injuries. They also enhance the sports environment and boost athletic enthusiasm. Depending on the raw materials used and the construction method, these tracks can be categorized as breathable, fully plastic, composite, and hybrid. Fully plastic polyurethane tracks are primarily made of two-component polyurethane, which offers air and water-tightness. Combining sports science and materials science, they fully meet the professional running track requirements of athletes. Component A of a fully plastic polyurethane track is typically a mixture of polyether polyols, plasticizers, chain extenders, dispersants, fillers, and pigments, while component B is a polyurethane prepolymer. Components A and B are mixed in a specific ratio with an appropriate amount of catalyst to initiate a cross-linking reaction, which then cures to form the fully plastic track. The largest amount of component A added to the all-plastic polyurethane plastic track is usually powder filler, which plays multiple roles, including: filling, which can reduce product costs and improve product competitiveness in the market; reducing the shrinkage of molded samples and improving the dimensional stability of products; adjusting the viscosity of the slurry; improving the impact strength, compression strength and wear resistance of the material; improving the coloring effect of the pigment and the light stability and chemical corrosion resistance of the finished product. On the other hand, when more powder is added to the all-plastic polyurethane plastic track material within a reasonable range, it often leads to a higher density of the molded site. To achieve a certain engineering thickness, more material is required. At the same time, the texture of this site is relatively hard, and the comfort of use is reduced. In order to alleviate the above problems, preparing a foamed polyurethane plastic track is one of the ideas. The usual practice for preparing a foamed polyurethane plastic track is to use part of the prepolymer (component B) to react with water to generate carbon dioxide bubbles in the system. This method has a significant effect on reducing the density and hardness of the field, but the foaming process is affected by many factors (Zhang Shihu, Shi Jingping, Zhao Yang, et al. Research on factors affecting the density of fully plastic polyurethane plastic track [J]. Polyurethane Industry, 2023, 38(3): 37-39.), and it is easy to lose control, so it is rarely used in actual engineering construction. In addition, more importantly, the above material foaming method forms an overall foam. The surface layer of this structure is easily damaged due to the presence of bubbles, especially after long-term water immersion, which greatly affects the service life of the field. Summary of the Invention

[0003] In response to the above technical problems, the present invention proposes a method for preparing a fully plastic polyurethane plastic track with controllable foaming at the bottom.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A method for preparing a fully plastic polyurethane track with controllable bottom foaming comprises adding water-soaked quartz sand to a polyurethane material A / B mixture. The method comprises the following steps: adding a curing catalyst, quartz sand, and a foaming catalyst to the polyurethane material A / B mixture, mixing thoroughly, spreading the mixture, and curing to form a fully plastic polyurethane track with controllable bottom foaming. The quartz sand requires pretreatment before use. The specific treatment method is: soaking the quartz sand in water for 0.5-1 hour, then draining the sand until no water droplets are noticeable.

[0006] Furthermore, the addition amount of the curing catalyst is 1.5-5‰ of the mass of the polyurethane A / B material mixture; the addition amount of the quartz sand is 1-20% of the mass of the polyurethane A / B material mixture; and the addition amount of the foaming catalyst is 0.3-2‰ of the mass of the polyurethane A / B material mixture.

[0007] Furthermore, the curing catalyst is a zinc-bismuth composite catalyst.

[0008] Furthermore, the quartz sand needs to be pre-treated before use. The specific treatment method is: soak the quartz sand in water for 0.5-1 hour, and then drain the quartz sand until no obvious water drops are discharged.

[0009] Furthermore, the foaming catalyst is dibutyltin dilaurate.

[0010] Furthermore, the polyurethane A / B material mixture is formed by mixing component A and component B in a mass ratio of 5:1.

[0011] Furthermore, the component A comprises, by mass, 15 parts of 330N, 7 parts of DL2000, 18 parts of chlorinated paraffin, 1.3 parts of MOCA, 1 part of red iron oxide, 0.3 parts of antioxidant, 0.15 parts of dispersant, 0.05 parts of defoaming agent, 26 parts of heavy calcium carbonate and 28 parts of talc;

[0012] The B component comprises, by weight, 40 parts of 330N, 17 parts of DL2000, 20 parts of chlorinated paraffin and 23 parts of MDI-50.

[0013] Furthermore, the preparation method of the component A is as follows: all raw materials are weighed by mass, stirred evenly, heated to 95-100° C. and vacuum-degassed and dehydrated for 4 hours. After dehydration, the temperature is lowered to 50-60° C., and the material is placed in a packaging barrel, sealed and stored.

[0014] The preparation method of the B component is as follows: 330N, DL2000 and chlorinated paraffin are weighed by mass, stirred evenly, heated to 95-100° C. and reduced to -0.09 MPa under vacuum degassing and dehydration for 2 hours. After dehydration, the temperature is lowered to 80-85° C., MDI-50 is added, and the temperature is maintained for 2.5 hours. When the temperature is lowered to 50-60° C., the material is placed in a packaging barrel, which is filled with nitrogen and sealed for storage.

[0015] The present invention also provides a fully plastic polyurethane rubber track with controllable bottom foaming, which is prepared by the above preparation method.

[0016] Compared with the prior art, the present invention has the following advantages and technical effects:

[0017] The density of the quartz sand and polyurethane A / B mixture is high. After the materials are spread, the water-soaked quartz sand in the system gradually sinks to the bottom of the site. Furthermore, the surface of the water-soaked quartz sand particles absorbs water, which reacts with some of the NCO groups in the polyurethane A / B mixture to form carbon dioxide bubbles. This causes the formation of bubbles to occur simultaneously with the curing of the material, trapping these bubbles at the bottom of the site. The upper portion of the site, devoid of quartz sand and adsorbed water, does not form a foamed structure. Therefore, the site prepared using this method can form a structure with a dense, firm upper layer and a foamed, soft, and elastic lower layer. The lower layer of the site prepared using this method can be controlled to foam according to actual needs. Furthermore, compared to sites prepared using traditional methods, the overall density is reduced, saving material. Furthermore, the site can achieve a soft bottom and hard top effect in a single construction step (previously, at least two construction or processing steps are required to achieve this structure), without the risk of overall foaming that can easily damage the site. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings, which constitute part of this application, are intended to provide a further understanding of this application. The exemplary embodiments and descriptions of this application are intended to explain this application and do not constitute an improper limitation on this application. In the accompanying drawings:

[0019] Figure 1 This is a schematic diagram of the preparation method of the fully plastic polyurethane plastic track with controllable foaming at the bottom of the present invention. DETAILED DESCRIPTION

[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0021] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.

[0022] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.

[0023] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be illustrative only.

[0024] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0025] The fully plastic polyurethane plastic track is simple to construct, has excellent performance, and a long service life, but the material cost is also high. In order to save material usage and improve the comfort of the site, a moderately foamed site can be prepared during project construction. One of the methods for preparing a foamed polyurethane plastic track is to use part of the prepolymer (component B) to react with water in the system to generate carbon dioxide bubbles. This method has a significant effect on reducing the density and hardness of the site, but the foaming process is easily affected by factors such as ambient temperature, air humidity, design index, catalyst dosage, water dosage, etc., and is very difficult to control. In addition, the foaming of materials prepared by current technology is all overall foaming. The surface layer of this structure is easily destroyed due to the presence of bubbles, especially after long-term immersion in water, which affects the service life of the site. At the same time, the site with this overall foaming structure often feels softer on the feet, affecting the comfort of use. Based on the above status quo, the present invention proposes a method for preparing a fully plastic polyurethane plastic track with controllable foaming at the bottom. The method for preparing a fully plastic polyurethane plastic track with controllable foaming at the bottom comprises the following steps:

[0026] (1) Preparation of component A: 15 parts of 330N, 7 parts of DL2000, 18 parts of No. 52 chlorinated paraffin, 1.3 parts of type II powdered MOCA, 1 part of red iron oxide, 0.3 parts of antioxidant 1010, 0.15 parts of dispersant from Yantai Sunshine Plastic Co., Ltd., 0.05 parts of defoaming agent from Yantai Sunshine Plastic Co., Ltd., 26 parts of 400 mesh heavy calcium carbonate and 28 parts of 400 mesh talc were stirred and dispersed uniformly, then heated to 95-100°C and reduced to -0.09 MPa under vacuum degassing and dehydration for 4 hours. After dehydration, cooled to 50-60°C, discharged, sealed and stored to obtain component A;

[0027] (2) Preparation of component B: 40 parts of 330N, 17 parts of DL2000 and 20 parts of No. 52 chlorinated paraffin were stirred and dispersed uniformly, then heated to 95-100°C and vacuumed to -0.09 MPa. Vacuum degassing and dehydration were performed for 2 hours. After dehydration, the temperature was lowered to 80-85°C, 23 parts of MDI-50 were added, the temperature was maintained for 2.5 hours, and the temperature was lowered to 50-60°C. The material was discharged and sealed with nitrogen to obtain component B.

[0028] (3) Preparation of polyurethane A / B material mixture: Component A and component B were mixed in a mass ratio of 5:1;

[0029] (4) Quartz sand pretreatment: Soak the quartz sand in water for 0.5-1h, then drain the quartz sand until no obvious water drops are seen;

[0030] (5) Add curing catalyst, quartz sand and foaming catalyst to the polyurethane A / B material mixture and spread it evenly. It can be cured and formed within 24 hours to obtain a fully plastic polyurethane plastic track with controllable foaming at the bottom.

[0031] In step (5) of some preferred embodiments of the present invention, the amount of the curing catalyst added is 1.5-5‰ of the mass of the polyurethane A / B material mixture, preferably 1.5-3‰; the amount of the quartz sand added is 1-20% of the mass of the polyurethane A / B material mixture, preferably 3-18%; the amount of the foaming catalyst added is 0.3-2‰ of the mass of the polyurethane A / B material mixture.

[0032] In step (5) of some preferred embodiments of the present invention, the curing catalyst is a zinc-bismuth composite catalyst (Shanghai Zhengui New Material Technology Co., Ltd.), which primarily catalyzes the crosslinking and curing of the polyurethane A / B material mixture. The foaming catalyst is dibutyltin dilaurate (T12, Shanghai Zhengui New Material Technology Co., Ltd.), which primarily catalyzes the reaction of NCO groups with water to form carbon dioxide gas.

[0033] The quartz sand used in the present invention is commercially available common quartz sand, and the particle size is preferably 80-160 mesh.

[0034] The above preparation method can be used to prepare a fully plastic polyurethane plastic track with controllable foaming at the bottom.

[0035] Unless otherwise specified, the "room temperature" in the present invention refers to 20-30°C.

[0036] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.

[0037] The raw materials used in the present invention are all purchased from the market.

[0038] The technical solution of the present invention is further illustrated by the following examples.

[0039] Figure 1 This is a schematic diagram of the preparation method of the fully plastic polyurethane plastic track with controllable foaming at the bottom of the present invention.

[0040] Examples 1-7

[0041] A fully plastic polyurethane runway with controllable foaming at the bottom is prepared according to the following steps:

[0042] (1) Preparation of component A: 15 parts of 330N, 7 parts of DL2000, 18 parts of No. 52 chlorinated paraffin, 1.3 parts of type II powdered MOCA, 1 part of red iron oxide, 0.3 parts of antioxidant 1010, 0.15 parts of dispersant from Yantai Sunshine Plastic Co., Ltd., 0.05 parts of defoaming agent from Yantai Sunshine Plastic Co., Ltd., 26 parts of 400 mesh heavy calcium carbonate and 28 parts of 400 mesh talc were stirred and dispersed uniformly, then heated to 95-100°C and reduced to -0.09 MPa under vacuum degassing and dehydration for 4 hours. After dehydration, the temperature was lowered to 50-60°C and sealed for storage to obtain component A.

[0043] (2) Preparation of component B: 40 parts of 330N, 17 parts of DL2000 and 20 parts of No. 52 chlorinated paraffin were stirred and dispersed uniformly, then heated to 95-100°C and reduced to -0.09 MPa under vacuum degassing and dehydration for 2 h. After dehydration, the temperature was lowered to 80-85°C, 23 parts of MDI-50 were added, the temperature was maintained for 2.5 h, and the temperature was lowered to 50-60°C and stored in a nitrogen-sealed container to obtain component B.

[0044] (3) Preparation of polyurethane A / B material mixture: Component A and component B were mixed in a mass ratio of 5:1;

[0045] (4) Quartz sand pretreatment: Soak the quartz sand in water for 1 hour, then drain the quartz sand until no obvious water drops are seen;

[0046] (5) Zinc-bismuth composite catalyst, treated quartz sand and dibutyltin dilaurate were added to the polyurethane A / B material mixture, mixed and spread, and the obtained sample was cured and formed at room temperature within 24 hours. After aging for 7 days, the sample state was observed and the sample density was measured.

[0047] The added amounts of zinc-bismuth composite catalyst, treated quartz sand, and dibutyltin dilaurate (the added amounts refer to the mass relative to the polyurethane A / B material mixture) are shown in Table 1, and the state of the obtained samples after aging for 7 days is shown in Table 2.

[0048] Table 1 Raw material addition amount of Examples 1-7

[0049]

[0050] Comparative Example 1

[0051] The same as Example 1, except that step (5) is as follows: adding a zinc-bismuth composite catalyst at a mass ratio of 3‰ of the polyurethane A / B material mixture to the polyurethane A / B material mixture, mixing and spreading, and the obtained sample is cured and formed at room temperature within 24 hours. After aging for 7 days, the sample state is observed and the sample density is measured (see Table 2).

[0052] Comparative Example 2

[0053] The same as Example 1, except that step (5) is as follows: adding 3‰ of the weight of the polyurethane A / B material mixture of zinc-bismuth composite catalyst, 1‰ of the weight of the polyurethane A / B material mixture of dibutyltin dilaurate, and 2‰ of the weight of the polyurethane A / B material mixture of water to the polyurethane A / B material mixture, mixing and spreading, and the obtained sample is cured and formed at room temperature within 24 hours. After aging for 7 days, the state of the sample is observed and the sample density is measured (see Table 2).

[0054] Comparative Example 3

[0055] Same as Example 1, except that the water-soaked quartz sand is replaced with water-soaked hollow glass microspheres.

[0056] Comparative Example 4

[0057] The same as Example 1, except that in step (5), the amount of water-soaked quartz sand added was 30% of the mass of the polyurethane A / B mixture. It was found that adding too much quartz sand significantly increased the viscosity of the material, and after the sample was completed, it showed a noticeable overall foaming effect.

[0058] Comparative Example 5

[0059] Same as Example 1, except that the quartz sand soaked in water is replaced with quartz sand that has not been soaked in water.

[0060] Table 2 Sample states and densities of Examples 1-7 and Comparative Examples 1-4

[0061]

[0062] The above are merely preferred embodiments of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.

Claims

1. A method for preparing a fully plastic polyurethane plastic track with controllable bottom foaming, characterized in that: Add quartz sand soaked in water to the polyurethane A / B material mixture.

2. The method for preparing the bottom controllable foaming all-plastic polyurethane plastic track according to claim 1, characterized in that: The preparation method specifically comprises the following steps: adding a curing catalyst, quartz sand and a foaming catalyst to a polyurethane A / B material mixture, spreading after mixing, and curing and forming, so as to obtain a fully plastic polyurethane plastic track with controllable foaming at the bottom; The quartz sand needs to be pretreated before use. The specific treatment method is: soak the quartz sand in water for 0.5-1h, and then drain the quartz sand until no obvious water drops are discharged.

3. The method for preparing the bottom controllable foaming all-plastic polyurethane plastic track according to claim 2, characterized in that: The added amount of the curing catalyst is 1.5-5‰ of the mass of the polyurethane A / B material mixture; the added amount of the quartz sand is 1-20% of the mass of the polyurethane A / B material mixture; and the added amount of the foaming catalyst is 0.3-2‰ of the mass of the polyurethane A / B material mixture.

4. The method for preparing the bottom controllable foaming all-plastic polyurethane plastic track according to claim 2, characterized in that: The curing catalyst is a zinc-bismuth composite catalyst.

5. The method for preparing the bottom controllable foaming all-plastic polyurethane plastic track according to claim 2, characterized in that: The foaming catalyst is dibutyltin dilaurate.

6. The method for preparing the bottom controllable foaming all-plastic polyurethane plastic track according to claim 2, characterized in that: The polyurethane A / B material mixture is prepared by mixing component A and component B in a mass ratio of 5:

1.

7. The method for preparing the bottom controllable foaming all-plastic polyurethane plastic track according to claim 6, characterized in that: The component A comprises, by weight, 15 parts of 330N, 7 parts of DL2000, 18 parts of chlorinated paraffin, 1.3 parts of MOCA, 1 part of red iron oxide, 0.3 parts of antioxidant, 0.15 parts of dispersant, 0.05 parts of defoamer, 26 parts of heavy calcium carbonate and 28 parts of talc; The B component includes, by weight, 40 parts of 330N, 17 parts of DL2000, 20 parts of chlorinated paraffin and 23 parts of MDI-50.

8. The method for preparing the bottom controllable foaming all-plastic polyurethane plastic track according to claim 7, characterized in that: The preparation method of the A component is as follows: weigh all raw materials by mass, stir them evenly, heat them to 95-100°C and reduce the negative pressure to -0.09Mpa, perform vacuum degassing and dehydration for 4 hours, and seal and store them after the dehydration is completed and the temperature is reduced to 50-60°C; The preparation method of the B component is as follows: 330N, DL2000 and chlorinated paraffin are weighed by mass, stirred evenly, heated to 95-100° C. and evacuated to -0.09 MPa, vacuum degassed and dehydrated for 2 hours, cooled to 80-85° C. after dehydration, added with MDI-50, kept at the temperature for 2.5 hours, and sealed and stored and nitrogen was introduced when the temperature was cooled to 50-60° C.

9. A fully plastic polyurethane plastic track with controllable bottom foaming prepared by the preparation method as described in any one of claims 1 to 8.